2022
DOI: 10.1126/scitranslmed.abg3072
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting N-glycan expression on tumor cells boosts chimeric antigen receptor T cell efficacy against solid malignancies

Abstract: Immunotherapy with chimeric antigen receptor (CAR)–engineered T cells showed exceptional successes in patients with refractory B cell malignancies. However, first-in-human studies in solid tumors revealed unique hurdles contributing to poor demonstration of efficacy. Understanding the determinants of tumor recognition by CAR T cells should translate into the design of strategies that can overcome resistance. Here, we show that multiple carcinomas express extracellular N-glycans, whose abundance negatively corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 75 publications
2
54
0
Order By: Relevance
“…This improved therapeutic potential was associated with increased CAR T cell expansion rates ( Figure 2C ), which were evident both in the CD4 + and CD8 + compartments ( Supplemental Figure 2E ), and with a trend toward higher release of IFN-γ, especially during the second antitumor response ( Figure 2D ). In line with our previous observations ( 34 , 35 ), CD8 + CAR T cells were enriched immediately after leukemia encounter in both conditions, while CD4 + CAR T cells became prominent at later time points ( Supplemental Figure 2F ). Notably, 14 days after infusion, CAR T N/SCM contained an increased T CM percentage compared with CAR T BULK ( Figure 2E ), possibly accounting for their superior and long-lasting therapeutic activity.…”
Section: Resultssupporting
confidence: 92%
“…This improved therapeutic potential was associated with increased CAR T cell expansion rates ( Figure 2C ), which were evident both in the CD4 + and CD8 + compartments ( Supplemental Figure 2E ), and with a trend toward higher release of IFN-γ, especially during the second antitumor response ( Figure 2D ). In line with our previous observations ( 34 , 35 ), CD8 + CAR T cells were enriched immediately after leukemia encounter in both conditions, while CD4 + CAR T cells became prominent at later time points ( Supplemental Figure 2F ). Notably, 14 days after infusion, CAR T N/SCM contained an increased T CM percentage compared with CAR T BULK ( Figure 2E ), possibly accounting for their superior and long-lasting therapeutic activity.…”
Section: Resultssupporting
confidence: 92%
“…As a result of this intrinsic alteration of surface protein glycosylation, some malignant cells may be predisposed to evade CAR binding. A recent report demonstrated this phenomenon in pancreatic cancer cells, wherein increased cellular glycosylation occurring through an unclear mechanism was associated with decreased CAR efficacy 27 . Interestingly, they found that disruption of N -acetylglucosaminyltransferase V (GnTV, encoded by MGAT5 ), a Golgi-resident glycosyltransferase that is a primary target of SPPL3 17 , improved the efficacy of CAR therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Instead, desialylation elicits stronger immunological synapse formation between the engaged T cells and target cells. Indeed, several studies published recently revealed that bulky glycans on the surface of tumor cells result in suboptimal synapse formation induced by both CAR-T cells and BiTEs (35).…”
Section: Discussionmentioning
confidence: 99%